Pteris melanocaulon Fée is an As hyperaccumulator - Claveria, Rene Juna R (Archīum Ateneo, 2019)
Pteris melanocaulon is noted to thrive very well in selected Cu–Au mines in the Philippines such as the Carmen Cu mine in Cebu and the Manila Mining Cu–Au mine in Surigao. Soil and plant samples were collected from field surveys as well as potted experiments. The computed bioaccumulation factor (BF) and translocation factor (TF) values from the analyses of As contents of the soil and the belowground and above ground components of the plant, apparently were comparable to known As hyperaccumulators Pteris vittata and Pityrogramma calomelanos. It is inferred with probability that the factors that influence the bioavailability of As as well as the uptake mechanisms for P. melanocaulon would be similar to the 2 known As hyperaccumulators. Previous works have noted P. melanocaulon as a very good Cu accumulator with very high Cu values in the belowground components and this study further identified it to be an excellent As hyperaccumulator with high As values in the aboveground components.